The Relationship Between Environmental Sanitation and Rat Density in Tanjung Uma Subdistrict, Working Area of Lubuk Baja Health Center, Batam City - Husein, Al Hafez; Herdianti, Herdianti; Yolanda Sari, Chinta; Siburian, Roliana (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: Rats can have a significant negative impact on public health as they can act as reservoirs for various pathogens that cause diseases in humans. One of the diseases associated with the presence of rats is Leptospirosis. Objective: This study aims to determine the relationship between environmental sanitation and rat density in Tanjung Uma Subdistrict, Batam City. Method: This study used a quantitative method with a cross-sectional approach. The population in this study consisted of all residents of Tanjung Uma Subdistrict, Batam City, with a sample size of 98 respondents. Statistical analysis was conducted using the chi-square test, and the research instrument was a questionnaire. Result and Discussion: The results of the study showed no relationship between the presence of garbage bins and rat density (p-value = 0.361); there was a relationship between accumulated garbage and rat density (p-value = 0.015); there was no relationship between the existence of water channels and rat density (p-value = 0.109); there was a relationship between wastewater drainage and rat density (p-value = 0.034). Conclusion: It can be concluded that there is a significant relationship between accumulated garbage and rat density in Tanjung Uma Subdistrict, Batam City.